Design of Automatic Lighting Installation Props Using Photocell and Motion Sensors - Rahmat, Syaputra; Islamida, Muhammad; Fachri, Raihan Rizal (JURNAL EDUNITRO Jurnal Pendidikan Teknik Elektro, 2024)
This teaching aid design approach is based on compiling learning materials that are fully necessary to achieve the desired understanding and skills. In the lighting installation subject, vocational electrical power installation techniques at SMK Negeri 2 Sinabang, there needs to be more demonstration media, which causes problems for students who find it very difficult to understand lighting installations and put them together. With this teaching aid medium, it is hoped that it can help students' understanding of installing lighting installations and improve student learning outcomes so that learning objectives are achieved. This teaching aid is designed to be a learning medium as a teacher's aids in teaching material on automatic lighting installations using photocell sensors and motion sensors in electrical power installation subjects. To determine the suitability of the props, a research instrument was made in the form of a media validation sheet, material validation, and questionnaire validation. The learning outcomes of students are known by providing several pre-test and post-test questions so that they can be used as a reference for how successful or appropriate the teaching aids are to be applied to students and lighting installation subjects. Based on the percentage results obtained from media expert validation, namely 89%, and material expert validation, namely 100% from the validator assessment, learning outcomes through the pre-test were 28% and the post-test 83%. The results obtained were based on validationÃ‚Â  showed "Very Feasible."